PEMIKIRAN IMAM TAQI AL-DIN AL-SUBKI (683/1284-756/1355) BERKAITAN KRITERIA KENAMPAKAN ANAK BULAN: Imam Taqī al-Dīn al-Subkī (683/1284-756/1355) on Criteria for Lunar Crescent’s Visibility Issues - Mohd Nawawi, Mohd Saiful Anwar; Wahid, Khairussaadah; Man, Saadan; Ahmad, Nazhatulshima; Abdul Niri, Mohammaddin (Jurnal Syariah, 2020)
Taqī al-Dīn al-Subkī (d. 756/1355) has been unreservedly credited as one of the scholars in the fiqh and usul al-fiqh. His most important scholarly work Adillah fī Ithbāt al-Ahillah, clearly demonstrates his sholarship in the sciences of lunar crescent’s visibility. It will then explore how his positions corresponds or are relevant to lunar crescent visibility criteria issues in the contemporary ages. This article concludes that al-Subkī views on those isues are still relevant to the some current issues related to lunar crescent’s visibility criteria.